Lower for Longer : Neutral Rates in the United States - Pescatori, Andrea (IMF Working Papers; Working Paper ;, 2015)
We use a semi structural model to estimate neutral rates in the United States. Our Bayesian estimation incorporates prior information on the output gap and potential output (based on a production function approach) and accounts for unconventional monetary policies at the ZLB by using estimates of 'shadow' policy rates. We find that our approach provides more plausible results than standard maximum likelihood estimates for the unobserved variables in the model. Results show a significant trend decline in the neutral real rate over time, driven only in part by a decline in potential growth whereas other factors (including excess global savings) matter. Neutral rates likely turned negative during the Global Financial Crisis and are expected to increase only gradually looking forward.